INFORMATION SUPPORT OF MODELING OF GRAVITY FUNCTION OF EMPLOYEES OF CITY SERVICE ENTERPRISES: Array - Chumachenko, I.; Davidich, N.; Galkin, A.; Davidich, Yu.; Kush, Y.; Samchuk, G. (Municipal economy of cities (Technical science), 2021)
The article is devoted to the establishment of information support to determine the patterns of changing the function of gravitation of employees of the urban-service enterprises. It has been established that the development of urban transport systems is impossible without the use of information technology to predict the parameters of the formation and absorption of passenger traffic. The design of urban transport systems cannot be achieved without assessing the impact of traffic improvement measures on changes in traffic and passenger flows. The main parameter by which it is possible to predict the choice of places of gravity by the inhabitants of cities is the function of gravitation between different areas of the city. The formalized functions of the gravitation of urban dwellers are not differentiated by the social composition of the population of cities. In addition, they use only travel time between areas of the city as an independent variable. The article proposes the formalization of the gravitation function of employees of the urban service enterprises using the parameters of the urban transport system, areas of departure and arrival, as well as the cost of movement. A special questionnaire has been developed to obtain the original information. A natural survey was carried out using it. As a result of the processing of survey data using correlation and regression analysis methods, the degree of influence of the studied factors on the value of the gravitation function of employees of urban service enterprises was revealed. Analysis of the correlation values obtained showed that the most significant impact on the value of the gravitation function of employees of urban services is the ratio of the cost of movement between districts and average wages in the city. The least impact is the distance from the area of residence to the place of application of work, the ratio of the cost of one square meter of housing in the area of residence and the average salary in the city, the ratio of the cost of one square meter of housing in the area of employment application and the average salary in the city. However, the compatible influence of all factors can change the level of influence of each factor and its combinations. In addition, it is advisable to take into account the technical and operational performance of urban passenger transport routes and individual transport routes.